2015
DOI: 10.2967/jnumed.115.156406
|View full text |Cite
|
Sign up to set email alerts
|

123I-MIBG Imaging for Prediction of Mortality and Potentially Fatal Events in Heart Failure: The ADMIRE-HFX Study

Abstract: ADMIRE-HF (AdreView Myocardial Imaging for Risk Evaluation in Heart Failure) established the prognostic significance of 123 Imetaiodobenzylguanidine ( 123 I-MIBG) imaging in heart failure subjects (median follow-up, 17 mo) using a composite endpoint dominated by heart failure progression. The ADMIRE-HF extension (ADMIRE-HFX) extended follow-up to a median of 24 mo and used mortality as the primary endpoint. The objective of these analyses was to use multiple multivariate risk modeling techniques to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
45
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 21 publications
0
45
0
2
Order By: Relevance
“…In light of the results from SHIFT and these other analyses, the paradigm of aiming for the highest tolerated dose of beta blocker may need to be shifted to aiming for a lower heart rate. This concept clearly warrants further prospective study.None of the studies mentioned previously assessed the prognostic value of cardiac 123 I‐ m IBG uptake, a measurement that has repeatedly been shown to be predictive 18, 25, 26, 27, 28, 29. The present study demonstrated the potential value of cardiac 123 I‐ m IBG uptake as a supplementary measure of sympathetic nervous system activity.…”
Section: Discussionmentioning
confidence: 52%
“…In light of the results from SHIFT and these other analyses, the paradigm of aiming for the highest tolerated dose of beta blocker may need to be shifted to aiming for a lower heart rate. This concept clearly warrants further prospective study.None of the studies mentioned previously assessed the prognostic value of cardiac 123 I‐ m IBG uptake, a measurement that has repeatedly been shown to be predictive 18, 25, 26, 27, 28, 29. The present study demonstrated the potential value of cardiac 123 I‐ m IBG uptake as a supplementary measure of sympathetic nervous system activity.…”
Section: Discussionmentioning
confidence: 52%
“…47 Several studies suggested new imaging-based biomarkers to assess the ventricular functions, such as late heartto-mediastinum ratio (HMR) during cardiac metaiodobenzylguanidine (MIBG) imaging in the ADRECARD study, or (123)I-metaiodobenzylguanidine ((123)I-MIBG) imaging in the ADMIRE-HF study (AdreView Myocardial Imaging for Risk Evaluation in Heart Failure). 48,49 The potential role of CMR-derived T1 mapping in evaluating myocardial fibrosis was demonstrated by several studies, which showed that this new biomarker can independently predict invasively measured LV stiffness. 50 …”
Section: Recent Imaging-based Biomarkersmentioning
confidence: 99%
“…These patients however composed only 5% of the study population. 19,20 Highest frequency of arrhythmic events occurred in patients with H/M ratio between 1.3 and 1.39. Patients with lower H/ M ratio did have higher mortality, suggesting the higher prevalence of non-arrhythmic causes of death, like pump failure and non-cardiac causes.…”
mentioning
confidence: 99%